The global growth of higher education philanthropy and fundraising (2019)
Individuals and cultures are generous around the world. Yet, formal philanthropy given by individuals manifests differently in diverse contexts, with various practices and traditions impacting giving (Bekkers, 2016). Plewes (2008) notes that although formal philanthropy is often thought of as a phenomenon of the Global North, recently there has been growth in formal philanthropic activity in the Global South. The Charities Aid Foundation’s World Giving Index (2017) found that nearly one-third (~30 per cent) of the world’s population donates money to others.